Sistema biométrico para automatizar el registro de asistencia docente en la unidad educativa ITSI del cantón Chone - Menéndez Chávez, Héctor Miguel (2016)
This work implemented a biometric system to automatize the teaching assistance registration in the ITSI educational unit of Chone canton through the technology of facial recognition. The SCRUM methodology was used which has five phases: Requirements, which used the technique of survey to obtain and learn how the process of teaching assistance registration was handled. Analysis, the results were analyzed using case study. Design, a logical design was made in Microsoft Power Point for the implementation of the system, in which the strategic points of cameras to be installed were determined. Evolution, when acquiring all the necessary specifications that entails the collection of requirements and analysis, for the development of the biometric system was realized the database design in which the entity-relationship model was used, selecting entities with their respective attributes. This was done with the database manager SQL SERVER 2012 and the development of the system was done in Visual Studio .Net. Delivery, the biometric system was implemented and obtained greater efficiency compared to the traditional system, since the teacher takes 5 minutes to enter and register their time of entry and exit from the institution, with the automatization system the biometric device detects it in 2 seconds and then recognizes it, obtaining its attendance report.